2014
DOI: 10.13065/jksdh.2014.14.02.181
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of oral health education by grade in some elementary school students

Abstract: Objectives : The purpose of this study is to investigate the effect of oral health education conducted by a dental hygienist in order to provide some information on intensive oral health education to elementary school students.Methods : Subjects were the students of J and M elementary schools in Seoul from October 28 to November 16, 2011. Oral health education was provided by a dental hygienist, and then they took the PHP test again to verify the effect of the oral health education. Results : Concerning change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Studies have reported that topics on OHE should be developed systematically based on grades and should be continuously provided to the students over the long term. 18 However, when it comes to oral health messages, textbooks are deficient in both content and extent, according to the conclusions of this study, even though the evidence is mostly true. The content analysis of core components for each standard is as follows.…”
Section: Discussionmentioning
confidence: 72%
“…Studies have reported that topics on OHE should be developed systematically based on grades and should be continuously provided to the students over the long term. 18 However, when it comes to oral health messages, textbooks are deficient in both content and extent, according to the conclusions of this study, even though the evidence is mostly true. The content analysis of core components for each standard is as follows.…”
Section: Discussionmentioning
confidence: 72%
“…Regular dental visits and dental examination experiences during this period help form good habits for dental care [4]. In addition, continuous and repeated oral health education is necessary to establish correct brushing and oral care habits as a self-administered oral health management method [5].…”
Section: Introductionmentioning
confidence: 99%